Co-processing potential of HTL bio-crude at petroleum refineries. Part 2: A parametric hydrotreating study. (1st February 2016) - Jensen, Claus Uhrenholt; Hoffmann, Jessica; Rosendahl, Lasse A.
Abstract: An experimental study on hydrotreatment of ligno-cellulosic hydrothermal liquefaction (HTL) bio-crude to achieve a bio-feed compatible for co-processing at a refinery was made to investigate the effect of operating temperature, pressure and hydrogen to oil ratio. Using a conventional NiMo/Al2 O3 hydrotreating catalyst at 350 °C and 337 NL H2 /L bio-crude, a promising bio-feed with 0.3 wt.% O, a HHV of 43.9 MJ/kg, a density of 894 kg/m 3 and an FT-IR spectra very similar to Northern Sea fossil crude oil was obtained. This work suggests that a gradual and sustainable phase-in of bio-feed through co-processing at existing refineries can be facilitated by intermediate hydrotreating of the bio-crude from hydrothermal liquefaction.